Facial Recognition AI Technology in Healthcare and the Law - Raposo, Vera Lúcia (2024)
Facial recognition technology - an artificial intelligence technology that analyses facial biometric data for different purposes - is being increasingly adopted in a variety of domains, including in healthcare. Within healthcare delivery, facial recognition can be used to analyse feelings and emotions, track potential health risks, diagnose medical conditions and identify individuals. Despite its various benefits in healthcare, it also poses legal and ethical risks, such as the possibility of erroneous results, bias and discrimination, and the potential violation of the rights of people affected by this technology. In the European Union, this technology is within the remit of so many European regulations - the General Data Protection Regulation, the Medical Devices Regulation and the future Artificial Intelligence Regulation - that compliance may be challenging. Faced with this legal entanglement, healthcare stakeholders might simply refrain from investing in this technology.